Blanca Varela’s justice and a note to an essay by Mario Montalbetti - Jiménez Moreno, Manuel de J. (2021)
This essay seeks literary and philological approaches to some central problems of the theory of law, such as the original meaning of justice and obedience to the legal norm. For this purpose, it will be analyzed the poem «Justicia» (Justice) by the Peruvian poet Blanca Varela, published in her poetry book Canto villano and the interpretation of the aphorism «la ley es la ley» (the law is the law) by Mario Montalbetti in El más crudo invierno (The harshest winter).